Tony Hancock dvd double feature: The Rebel (directed by Robert Day) + the Punch and Judy Man (Directed by Jeremy Summers) - Day, Robert; Summers, Jeremy; Hancock, Tony ([S.l.] : Studio Canal, 2003)
Two vintage comedies featuring the joker from East Cheam. In The rebel, Tony Hancock plays a frustrated creative artist and bored city clerk who decides to escape across the channel to Paris. In The Punch and Judy man, Hancock is the melancholy title character who tries to establish himself as an important citizen in the seaside town where he works.
Bevat: The Rebel (ca. 101 min.) -- The Punch and Judy man (ca. 89 min.).
Engels gesproken, niet ondertiteld
film
Keywords: Hancock, Tony; Day, Robert; Summers, Jeremy